Entre o social e o moral: o suicídio na literatura e a sociedade do Brasil na virado do século XIX - Gaspar, Lucas Eduardo (2024)
This thesis will present some paths and debates for understanding suicide as a relevant object in the construction of historical knowledge. Considering that its practice and the meanings constructed around it can be read as a real part of the context in which they are inserted. In this sense, we emphasize a reading of suicide as a social and moral practice, thus emphasizing how its narratives or references are intertwined with power relations and the construction of social mentalities. From this, we outline some paths for carrying out this exercise. We selected for the debate the experience of Brazilian society at the turn of the 19th to the 20th century. Because, in addition to being one of the few periods in which we can find sufficient sources for the composition of an in-depth analysis, it is in this context that important changes and continuities in Brazilian society are delimited. National literary production then presented itself as a material that allowed access to a variety of narratives, references and meanings of suicide, as well as several of these social faces contained in its composition. For this, several works and authors were used as sources, which composed different perspectives and diversified the meanings surrounding suicide. Since this is a topic that is still unusual in the field of History, we dedicated the beginning of this work to presenting the historicity of the topic, discussing how it took on different contours in various periods. Along the way, we were able to problematize some of its most common definitions and, at the same time, compose our own framework of references in its analysis. In the following three chapters, we endeavor to analyze our object of study – the issue of suicide – based on its own presence and importance in the composition of some historical themes such as: The influence of the themes of death and suicide in the constitution of the country's dominant classes; Religious interest in controlling the discourses and values surrounding the practice; and, finally, discussing the dynamics of interaction between suicide and the field of human feelings, also as evidence of social impositions and limits.